2021
DOI: 10.1093/annweh/wxab025
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, Facilitating Factors, and Barriers in Using Personal Dosimeter among Medical Radiation Workers in a Middle-Income Asian Setting

Abstract: This qualitative study explores the medical radiation workers’ (MRWs) beliefs with the support of the theory of planned behaviour’s constructs regarding the use of personal dosimeters in order to identify the facilitating factors and barriers to practising good personal dose monitoring. The exploration was conducted through semi-structured face-to-face interviews with 63 MRWs from the public, private, and university hospitals. Belief statements from the informants were organized under the behavioural, normativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Past studies revealed that MRWs lost motivation to use or change dosimeters regularly because they have lost the purpose of using the device due to the unknown status of their exposures (Botwe et al 2015; Mohd Ridzwan et al 2021a). However, a past study recorded that the data were kept and only communicated to those with unusual exposures (Mohd Ridzwan et al 2021b), probably to save resources and protect the confidentiality of the data.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Past studies revealed that MRWs lost motivation to use or change dosimeters regularly because they have lost the purpose of using the device due to the unknown status of their exposures (Botwe et al 2015; Mohd Ridzwan et al 2021a). However, a past study recorded that the data were kept and only communicated to those with unusual exposures (Mohd Ridzwan et al 2021b), probably to save resources and protect the confidentiality of the data.…”
Section: Discussionmentioning
confidence: 99%
“…This psychometric tool can also measure the factors that are barriers to consistent dosimeter use, such as the workers’ tasks. For instance, some respondents only worked under low radiation exposure and perceived using dosimeters as being pointless (Mohd Ridzwan et al 2021a). Meanwhile, those who constantly worked with higher radiation procedures avoided using the device so that they were not forced to take radiation leave or be denied work (Botwe et al 2015; Rose et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations